A cost effective management system for prevention of oil / grease to receiving water - Colline, John (Universiti Malaysia Sarawak (UNIMAS), 2000)
This dissertation investigates an alternative cost-effective method to remove oil/grease from the receiving water. The objective and the methodology are divided into two phases where; Phase 1. is to design, develop and to fabricate a novel cost effective technology for removing oill grease! solids from the wastewater. Thus a general idea of the parallel plate separator and a few principal factors as well as the design information was applied. Phase 2 is to evaluate the performance and the effectiveness of the removal system in generating an effluent of acceptable and an experiment was done and an analysis of 'Characteristic Wet Analysis' was conducted to analyze the oil/grease content From the experiment, the average influent concentration of oil/grease is 38,325 mglL. While the average effluent concentration of oil/grease is 49.125 mglL and hence, the concentration level of oillgrease is 0.13%. This shown that the removal efficiency of oil/grease is 99.87% which is within the acceptable quality of an effluents.